2011
DOI: 10.1183/09031936.00057811
|View full text |Cite
|
Sign up to set email alerts
|

Validity of an automated telephonic system to assess COPD exacerbation rates

Abstract: Current tools for recording chronic obstructive pulmonary disease (COPD) exacerbations are limited and often lack validity testing. We assessed the validity of an automated telephonic exacerbation assessment system (TEXAS) and compared its outcomes with existing tools.Over 12 months, 86 COPD patients (22.1% females; mean age 66.5 yrs; mean postbronchodilator forced expiratory volume in 1 s 53.4% predicted) were called once every 2 weeks by TEXAS to record changes in respiratory symptoms, unscheduled healthcare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…Although this may account for some of the discrepancy in the time spent in exacerbations, our previous study demonstrated TEXAS to be a valid measure to assess exacerbation frequency. 21 Our mean exacerbation frequency does correspond with the findings of Erdal et al, 22 who found a median exacerbation frequency of four in their hospital-recruited COPD patients.…”
Section: Discussionsupporting
confidence: 91%
“…Although this may account for some of the discrepancy in the time spent in exacerbations, our previous study demonstrated TEXAS to be a valid measure to assess exacerbation frequency. 21 Our mean exacerbation frequency does correspond with the findings of Erdal et al, 22 who found a median exacerbation frequency of four in their hospital-recruited COPD patients.…”
Section: Discussionsupporting
confidence: 91%
“…Results did not show any reduction in hospital admissions or improvement in quality of life [12]. However, there have been some tools such as TEXAS and EXACT to quantify and measure exacerbations in patients with COPD patients [15,16]. The validity of TEXAS, an automated telephonic exacerbation assessment system which records symptoms and use of medication, has been assessed.…”
Section: Resultsmentioning
confidence: 99%
“…The study was carried out on 86 patients with COPD. The results showed that TEXAS, when compared with other tools such as a paper diary or medical record review, showed the highest detected rates of exacerbations and patients’ compliance in providing exacerbation-related information [16]. The EXACT daily diary was designed to standardize the process for assessing acute exacerbations of patients with COPD by providing a direct measure of patient-reported symptoms of exacerbation [15].…”
Section: Resultsmentioning
confidence: 99%
“…Walters et al24 investigated diary-keeping in COPD and ascertained the items that best predicted emergency attendances for exacerbations. They conclude that good compliance can be achieved using daily diaries in COPD, although this is worse in those with poor educational level, whereas Bischoff et al25 report that an automated telephonic exacerbation assessment system is a valid tool to assess COPD exacerbation rate in prospective clinical study. In this study, we not only used diaries but also systematically asked patients every month to minimize recall bias.…”
Section: Discussionmentioning
confidence: 99%